Targeting Staphylococcus aureus dominated skin dysbiosis in actinic keratosis to prevent the onset of cutaneous squamous cell carcinoma: Outlook for future therapies? - Bromfield, Jacoba Isobella; Hugenholtz, Philip; Frazer, Ian Hector; Khosrotehrani, Kiarash; Chandra, Janin (Frontiers in Oncology, 2023)
Cutaneous squamous cell carcinoma (cSCC) and its premalignant precursor, actinic keratosis (AK), present a global health burden that is continuously increasing despite extensive efforts to promote sun safety. Chronic UV exposure is a recognised risk factor for the development of AK and cSCC. However, increasing evidence suggests that AK and cSCC is also associated with skin microbiome dysbiosis and, in particular, an overabundance of the bacterium Staphylococcus aureus (S. aureus). Studies have shown that S. aureus-derived toxins can contribute to DNA damage and lead to chronic upregulation of proinflammatory cytokines that may affect carcinogenesis. Eradication of S. aureus from AK lesions and restoration of a healthy microbiome may therefore represent a therapeutic opportunity to alter disease progression. Whilst antibiotics can reduce the S. aureus load, antibiotic resistant S. aureus pose an increasing global public health threat. The use of specific topically delivered probiotics has been used experimentally in other skin conditions to restore eubiosis, and could therefore also present a non-invasive treatment approach to decrease S. aureus colonisation and restore a healthy skin microbiome on AK lesions. This article reviews mechanisms by which S. aureus may contribute to cutaneous carcinogenesis, and discusses hypotheses and theories that explore the therapeutic potential of specific bacterial species which compete with S. aureus in an attempt to restore microbial eubiosis in skin.